PENGARUH SEMANGAT KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BATAM TELEVISI - Muhammad Sidik; Sumardin (LPPM Universitas Ibnu Sina, 2023)
The author conducted research at the Batam Television Office in Batam City. The purpose of this study is to find out how the performance of employees at the Batam Television Office is. Respondents from the study were 41 respondents, all of whom were permanent employees. The research was conducted for 3 months, namely November-January 2023. The data collection method in this study was to use a questionnaire. And this type of research is quantitative research, with the data analysis tool used is SPSS 17.0. In this study, it consists of three independent variables, namely work enthusiasm, work motivation and work environment, and one dependent variable, namely employee performance. The results of the study, when viewed from the ANOVA test, produce a calculated F number of 101,211> F table 2.87 with H1 accepted. This means that the regression coefficient of Morale, Work Motivation and Work Environment simultaneously affect the Performance of Batam Television Employees in Batam City.